Future 5G platform ecosystems: Case study of a digitalized port stakeholders' new interactions and value configurations - Petri Ahokangas; Marja Matinmikko-Blue; Seppo Yrjölä; Heikki Hämmäinen (International Telecommunications Society (ITS), 2020)
Data and connectivity platforms play a key role in the digitalization of different sectors of our society. The availability of new services that are specialized to the needs of a given vertical sector in a specific location can significantly boost the business opportunities of that ecosystem. 5G in particular is aiming at offering new building blocks to digitalization by enabling fast exchange of increasing amounts of data between different entities. This paper presents a case study of the digitalization of a port which presents an intriguing example of future 5G platform ecosystems. We identify the key stakeholders of the port ecosystem and characterize their interactions in the current situation. We depict and analyze alternative configurations for connectivity and data platforms encompassing centralized, hybrid and fragmented approaches. Finally, we propose three consecutive steps for managing the service roadmap of the converged connectivity and data platforms in the port: fragmented data - fragmented connectivity phase, fragmented data - hybrid connectivity phase and the optimally hybrid data - optimally centralized connectivity phase.
Keywords: 330